Social service offices as a point of entry into substance abuse treatment for poor South Africans - Burnhams Nadine; Dada Siphokazi; Myers Bronwyn (Substance Abuse Treatment, Prevention, and Policy, 2012)
Abstract Background In South Africa, district social service offices are often the first point of entry into the substance abuse treatment system. Despite this, little is known about the profile of people presenting with substance-related problems at these service points. This has a negative impact on treatment service planning. This paper begins to redress this gap through describing patterns of substance use and service needs among people using general social services in the Western Cape and comparing findings against the profile of persons attending specialist substance abuse treatment facilities in the region. Methods As part of a standard client information system, an electronic questionnaire was completed for each person seeking social assistance. Data on socio-demographic characteristics, the range of presenting problems, patterns of substance use, perceived consequences of substance use, as well as types of services provided were analysed for the 691 social welfare clients who reported substance use between 2007 and 2009. These data were compared against clients attending substance abuse treatment centres during the same time period. Results Findings indicate that social services offices are used as a way of accessing specialist services but are also used as a service point, especially by groups under-represented in the specialist treatment sector. Women, people from rural communities and people with alcohol-related problems are more likely to seek assistance at social service offices providing low threshold intervention services than from the specialist treatment sector. Conclusions The study provides evidence that social services are a point of entry and intervention for people from underserved communities in the Western Cape. If these low-threshold services can be supported to provide good quality services, they may be an effective and efficient way of improving access to treatment in a context of limited service availability.